1998
DOI: 10.1046/j.1365-2958.1998.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest in Era GTPase mutants: a potential growth rate‐regulated checkpoint in Escherichia coli

Abstract: SummaryEra is a low-molecular-weight GTPase essential for Escherichia coli viability. The gene encoding Era is found in the rnc operon, and the synthesis of both RNase III and Era increases with growth rate. Mutants that are partially defective in Era GTPase activity or that are reduced in the synthesis of wild-type Era become arrested in the cell cycle at the predivisional two-cell stage. The partially defective Era GTPase mutation (era1) suppresses several temperature-sensitive lethal alleles that affect chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
160
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(166 citation statements)
references
References 45 publications
5
160
1
Order By: Relevance
“…Remarkable equality between expression of RNase III and Era, the product of the second gene in the three-gene rnc operon, suggest that rnc and era are transcriptionally and translationally coupled Matsunaga et al, 1996). The recent identification of Era as a potential cell cycle regulator (Britton et al, 1997; indicates that RNase III and Era may collaborate to tie the growth rate to the cell cycle through their tightly linked co-expression (Britton et al, 1998).…”
Section: Regulation Of the Rnc Operonmentioning
confidence: 99%
“…Remarkable equality between expression of RNase III and Era, the product of the second gene in the three-gene rnc operon, suggest that rnc and era are transcriptionally and translationally coupled Matsunaga et al, 1996). The recent identification of Era as a potential cell cycle regulator (Britton et al, 1997; indicates that RNase III and Era may collaborate to tie the growth rate to the cell cycle through their tightly linked co-expression (Britton et al, 1998).…”
Section: Regulation Of the Rnc Operonmentioning
confidence: 99%
“…Later, detailed sequence analysis suggested that Era is not a RAS-like protein (Chen et af., 1990). Recently, a human homologue of Era was reported that is distincr from RAS proteins (Britton et al, 1998 The GenBank accession number for the nucleotide sequence of the Streptococcu:: pneumoniae era gene is AF07281. negative bacteria, and Mycopfasma spp. (Ahnn et al, 1986;Fleischmann et al, 1995;Fraser et al, 1995;Kawabata et al, 1997;Zuber et al, 1990Zuber et al, , 1997, and is essential for bacterial growth (Gollop & March, 1991b;Inada et al, 1989;March et al, 1988;Sat0 et al, 1998;Takiff et al, 1989Takiff et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biochemical basis for their failure to complement the E. coli era mutants remains unknown as biochemical characterization of these mutant Era proteins was not described Pillutla et a!., 1995). Genetic studies showed that depletion of the cellular amount of Era inhibited the growth of E. coli cells and caused the cells to elongate (Britton et al, 1997(Britton et al, , 1998Gollop & March, 1991b;March et al, 1988). Also, the viability of these cells was drastically reduced upon repression of Era production (Gollop & March, 1991b;Lerner & March, 1991 ;March et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elongated cells contained two or four segregated nucleoids [3,4]. In addition, a mutant allele of E. coli era suppressed several temperaturesensitive alleles of the genes affecting chromosome replication and partitioning [3,4]. Thus, Era plays a role in DNA replication and cell cycle progression.…”
mentioning
confidence: 99%